Silver nanoparticles enhanced photoluminescence of Nd3+ doped germanate glasses at 1064 nm - Kassab, Luciana R.P. [UNESP]; Silva, Davinson M. [UNESP]; Garcia, José A.M.; da Silva, Diego S.; de Araújo, Cid B. (Elsevier, 2016)
Infrared photoluminescence (PL) properties of PbO-GeO2 glasses containing neodymium ions (Nd3+) and silver nanoparticles (NPs) were investigated. The excitation was made with a continuous-wave diode laser operating at 805 nm, in resonance with the Nd3+ transition 4I9/2 → 4F5/2. Growth of ∼160% in the PL intensity at 1064 nm, was observed in comparison with a reference sample without silver NPs. The PL enhancement is attributed to the increased local-field in the Nd3+ locations nearby the NPs. The present results indicate that PbO-GeO2 glasses containing Nd3+ and silver NPs have good prospect to be used in optical amplifiers at 1064 nm.
Keywords: Heavy-metal oxide glasses; Infra-red photoluminescence; Metallic nanoparticles